Answer:
The correct option is;
Use a scale factor of 2
Step-by-step explanation:
The parameters given are;
A = (1, -6)
B = (5, -6)
C = (6, -2)
D = (0, -2)
A'' = (1.5, 4)
B'' = (3.5, 4)
C'' = (4, 2)
D'' = ( 1, 2)
We note that the length of side AB in polygon ABCD = √((5 -1)² + (-6 - (-6))²) = 4
The length of side A''B'' in polygon A''B''C''D'' = √((3.5 -1.5)² + (4 - 4)²) = 2
Which gives;
AB/A''B'' = 4/2 = 2
Similarly;
The length of side BC in polygon ABCD = √((6 -5)² + (-2 - (-6))²) = √17
The length of side B''C'' in polygon A''B''C''D'' = √((4 -3.5)² + (2 - 4)²) = (√17)/2
Also we have;
The length of side CD in polygon ABCD = √((6 -0)² + (-2 - (-2))²) = 6
The length of side C''D'' in polygon A''B''C''D'' = √((4 -1)² + (2 - 2)²) = 3
For the side DA and D''A'', we have;
The length of side DA in polygon ABCD = √((1 -0)² + (-6 - (-2))²) = √17
The length of side D''A'' in polygon A''B''C''D'' = √((1.5 -1)² + (4 - 2)²) = (√17)/2
Therefore the Polygon A B C D can be obtained from polygon A''B''C''D'' by multiplying each side of polygon A''B''C''D'' by 2
The correct option is therefore;
Use a scale factor of 2.
Answer:
it looks hard
Step-by-step explanation:
Answer:
Expected value of the game: -$0.421
Expected loss in 1000 games: $421
Step-by-step explanation:
There are two possible outcomes for the event:
- There is a 1 in 38 chance of winning $280
- There is a 37 in 38 chance of losing $8
The expected value for a single game is:

The expected value of the game is -$0.421
In 1,000 plays, the expected loss is:

You would expect to lose $421.
It will be around 1.6metres
hope it helps
Answer:
First, let's define an arithmetic sequence:
In an arithmetic sequence, the difference between any two consecutive terms is always the same.
Then we can write it in a general way as:
aₙ = a₁ + (n - 1)*d
where:
aₙ is the n-th term of the sequence.
d is the constant difference between two consecutive terms.
a₁ is the initial term of our sequence.
Now in this case we know that the first terms of our sequence are:
84, 77, ...
Then we know the initial term of our sequence:
a₁ = 84.
And the value of d can be calculated as:
d = a₂ - a₁ = 77 - 84 = -7
Then the general way of writing this sequence is:
aₙ = 84 + (n - 1)*(-7)
And the recursion relation is:
aₙ = aₙ₋₁ - 7
So for the n-th term, we must subtract 7 of the previous term.